Sex Difference in Trigeminal Neuropathic Pain Response to Exercise: Role of Oxidative Stress. (29th June 2020) - Rostami, Zahra; Ghasemi, Sahar; Farzadmanesh, Hamed; Safari, Manouchehr; Ghanbari, Ali
Abstract : Aim . Orofacial chronic neuropathic pain commonly occurs following trigeminal nerve injuries. We investigated whether swimming exercise can reduce trigeminal neuropathic pain through improving antioxidant capacity. Materials and Methods . Twenty-eight Wistar rats of either sex and 180–220 grams were divided into 4 groups as sham, neuropathy, neuropathy + single bout exercise, and neuropathy + 2 weeks of exercise. Trigeminal neuropathy was carried out through chronic constriction injury (CCI) of infraorbital nerve. Protocols of exercise were included a single bout session (45 minutes) and a 2-week (45 minutes/day/6 days a week) swimming exercise. Mechanical allodynia was detected using Von Frey filaments. The activity of the serum antioxidant enzymes glutathione peroxidase and superoxides dismutase was assayed using ELISA kits. Results . We found that CCI significantly reduced facial pain threshold in both sexes (P < 0.05 ). Both swimming exercise protocols significantly reduced mechanical allodynia in female rats compared to the sham group; however, only 2 weeks of exercise were significantly effective in male rats. The activity of antioxidant enzyme glutathione peroxidase significantly (P < 0.05 ) decreased following CCI in female rats against that in the sham group and 2-week exercise significantly (P < 0.05 ) increased it toward the control level. The levels of glutathione peroxidase in male rats and superoxidase dismutase in both sexes were not significantly different compared to their sham groups. Conclusion . Swimming exercise alleviates trigeminal neuropathic pain in both sexes. Oxidative stress as a possible mechanism was involved in the effect of exercise on female rat trigeminal neuropathy.